2019
DOI: 10.1590/1678-9199-jvatitd-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

BthTX-I from Bothrops jararacussu induces apoptosis in human breast cancer cell lines and decreases cancer stem cell subpopulation

Abstract: Background: Breast cancer is the neoplasm with both the highest incidence and mortality rate among women worldwide. Given the known snake venom cytotoxicity towards several tumor types, we evaluated the effects of BthTX-I from Bothrops jararacussu on MCF7, SKBR3, and MDAMB231 breast cancer cell lines. Methods: BthTX-I cytotoxicity was determined via MTT [3-(4,5-dimethylthiazol-2yl)-2,5-diphenyl-tetrazoliumbromide] assay. Cell death was measured by a hypotonic fluorescent solution method, annexin-V-FITC/propidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In this context, this study indicated that GNP-NN 32 was capable of inducing apoptosis at a concentration of 1.5 μg/mL in MCF-7 cell line and 5 μg/mL in MDA-MB-231 cell line. Our results are in agreement with other studies that discovered that disintegrin from Crotalus durissus collilineatus venom induced cytotoxicity [37] whereas BthTX-I from Bothrops jararacussu induced apoptosis [38] and also showed antitumor and antimetastatic effects [39] on human breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…In this context, this study indicated that GNP-NN 32 was capable of inducing apoptosis at a concentration of 1.5 μg/mL in MCF-7 cell line and 5 μg/mL in MDA-MB-231 cell line. Our results are in agreement with other studies that discovered that disintegrin from Crotalus durissus collilineatus venom induced cytotoxicity [37] whereas BthTX-I from Bothrops jararacussu induced apoptosis [38] and also showed antitumor and antimetastatic effects [39] on human breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, the spontaneous apoptosis rate for SKBR3 cells cultured in RPMI 1640 medium over 24 h was 15 ± 6%. 8 Here, cells with DNA that migrated greater than 126 μm, the minimum migration distance of the DNA ladder, were classified as apoptotic. We observed an apoptosis rate of 0.6% (i.e., 8 cells exhibited fragmented DNA out of 1394 cells; n = 3 chips).…”
Section: Resultsmentioning
confidence: 99%
“… 7 Bulk proteoform measurements have been made with standard Western blots to investigate the apoptosis pathways after dosing with specific drugs/chemicals. 8 10 …”
Section: Introductionmentioning
confidence: 99%
“…Metalloproteases, serine proteases, LAAOs, and PLA2s are some of the most abundant proteins present in bothropic venoms, and the toxic action of these proteins are responsible for myotoxic effects, disruption in the coagulation cascade through thrombin-like proteins (serine proteases), imbalance in the blood homeostasis by the action of some metalloproteinases, apoptosis induction, and changes in the protein expression in oxidative stress and energy metabolism by the increase of Ca 2+ influx. Several studies have revealed that these enzymes are critical regulators of cancer pathologies in several types of cancers including breast cancer [ 121 , 122 , 123 , 124 , 125 , 126 , 127 ]. Moreover, it has been previously shown that B. jararaca venom may have an important antitumor effect on Ehrilich ascites tumor cells in vivo and in vitro [ 36 ].…”
Section: Discussionmentioning
confidence: 99%